IDENTIFIKASI JAMUR ENDOFIT YANG BERASOSIASI DENGAN DAUN JERUK LIMAU Citrus x amblycarpa (Hassk.) OCHSE DI KEBUN KALPATARU, DENPASAR, BALI - Riswara Nurfitri; Junita Hardini; I Ketut Muksin (Program Studi Biologi Universitas Udayana, 2024)
Endophytic fungi are fungi that live and associate in host plants and have the potential to produce secondary metabolites that are the same as their host. Utilization of endophytic fungi as a solution reduces the use of a lot of biomass to produce the desired secondary metabolites. This study aims to explore and identify endophytic fungi found on lime leaves obtained from Kalpataru plantation, Denpasar, Bali. Endophytic fungi were isolated from samples of young and mature leaves that were fresh, not wilted or yellow, and disease free. Fungal isolation was carried out by direct planting method on Potato Dextrose Agar (PDA) media at room temperature (27oC), and the incubation time was 3-7 days. Re-isolation was carried out to obtain pure cultures, then the endophytic fungi were identified by observing the morphological characters macroscopically and microscopically, then compared with identification books. The results obtained were eight isolates, and six isolates were identified belonging to the genera Fusarium, Colletotrichum, Aspergillus, Penicillium, and 2 isolates were not identified (sterile mycelia). Endophytic fungi found on young leaves, namely Aspergillus and Colletotrichum, on mature leaves, namely Fusarium, Aspergillus, and Penicillium. Keywords: endophytic fungi, lime, sterile mycelia, PDA